2014
DOI: 10.5588/pha.14.0035
|View full text |Cite
|
Sign up to set email alerts
|

Management of multi- and extensively drug-resistant tuberculosis in Ukraine: how well are we doing?

Abstract: A tertiary care facility in Ukraine, a high multiand extensively drug-resistant tuberculosis (MDR/ XDR-TB) burden country. Objectives: To assess the management and treatment outcomes of MDR, pre-XDR-TB and XDR-TB. Design: Cohort study using programme data, 2006-2011. Results: Of 484 individuals with drug-resistant TB, 217 (45%) had MDR-, 153 (32%) pre-XDR-and 114 (24%) XDR-TB. Of all resistant types completing the intensive phase of treatment, 322 (67%) were alive and had culture converted. This included 157 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
4
11
0
Order By: Relevance
“…Compared with adults with MDR-TB in Ukraine, the children in our cohort had much better treatment outcomes [11,12]. This finding is consistent with those conducted in other settings that have reported higher rates of MDR-TB treatment success in children compared with adults [3].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with adults with MDR-TB in Ukraine, the children in our cohort had much better treatment outcomes [11,12]. This finding is consistent with those conducted in other settings that have reported higher rates of MDR-TB treatment success in children compared with adults [3].…”
Section: Discussionsupporting
confidence: 90%
“…Despite the country's high MDR-TB burden, few reports have described the treatment of this disease in Ukraine [11,12]. Two recent studies showed that only 18-22% of adults treated for MDR-TB achieved treatment success, defined as cured or treatment completion [11,12]. This rate is far lower than the global treatment success rate of 54% among adults [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 As per N. Lytvynenko et al (Ukraine), Cured (19%), treatment completed (1%), failure (16%), died (2%), and lost to follow up (16%). 6 Most of the studies have similar findings except treatment failure. The difference may be because of study design, place and implementation of program.…”
Section: Resultsmentioning
confidence: 68%
“…Doing so will also limit disruptions related to frequent turnover of government officials which was highlighted as a perceived challenge. Of recent Ukraine has articulated "what must change" in terms of current management approaches [21][22][23].…”
Section: Uncertaintymentioning
confidence: 99%